2004
DOI: 10.1111/j.1365-2672.2004.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and purification of acidocin CH5, a bacteriocin produced by Lactobacillus acidophilus CH5

Abstract: Aims: To characterize and to purify a bacteriocin produced by Lactobacillus acidophilus strain with its activity restricted to Gram-positive bacteria. Methods and Results: Native acidocin CH5, a bacteriocin produced by L. acidophilus CH5 an isolate from a dairy starter culture forms in MRS (Oxoid, Basingstoke, UK) broth high-molecular weight aggregates which can dissociate into smaller units (retained by 5 kDa membrane) with higher activity. Acidocin CH5 was purified using combinations of chromatographic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
0
26
0
3
Order By: Relevance
“…Such a synergistic inhibition has been shown between nisin on the one hand and garlic extract or thymol on the other. Chumchalova´ et al (2004) reported that the partial purification and characterization of heat-stable acidocin CH5, a bacteriocin produced by L. acidophilus CH5, showed that the active compound caused fast decrease in viable cell count of the indicator strain Lactobacillus delbrueckii subsp. lactis LTI30 which was in accordance to results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such a synergistic inhibition has been shown between nisin on the one hand and garlic extract or thymol on the other. Chumchalova´ et al (2004) reported that the partial purification and characterization of heat-stable acidocin CH5, a bacteriocin produced by L. acidophilus CH5, showed that the active compound caused fast decrease in viable cell count of the indicator strain Lactobacillus delbrueckii subsp. lactis LTI30 which was in accordance to results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics allow the development of a scale-up process for the purification of this bacteriocin. Acidocin CH5, produced by L. acidophilus, was purified by using combinations of chromatographic methods based on hydrophobic and cation exchange principles (Chumchalova et al, 2004). Acidocin D20079, produced by L. acidophilus DSM 20079, was purified by ammonium sulphate precipitation followed by sequential cation exchange (Carboxymethyl Sepharose column), dialysis and hydrophobic interaction chromatography (Octyl Sepharose column), followed by electrophoresis (SDS-PAGE) (Deraz et al, 2005).…”
Section: Purification Of Class I Bacteriocinsmentioning
confidence: 99%
“…Generally, the first step is a precipitation with ammonium sulphate [29] or an aqueous extraction of secreted compounds by medium acidification to release cationic compounds bound to the bacteria cell wall [27]. An obvious strategy for the enrichment of those cationic antimicrobial peptides and proteins is a fractionation by ion-exchange chromatography [5,6,11].…”
Section: Introductionmentioning
confidence: 99%